« Confins », traductions, échos et connotations - Confins (Confins)
The title of this journal, Confins, was chosen for several convergent reasons: to be understandable in both Portuguese and French, the two main languages of the journal, to have only positive (or at least neutral) connotations in the two languages, to evoke the theme of pioneer fronts and the frontiers of science, where progress is made, where happen the most fruitful exchanges.To continue and deepen this reflection the article explores synonyms, antonyms, echoes and connotations of the word in French and Portuguese, but also in various European languages (Spanish, Italian, German, Romanian), first from French then Portuguese, and situates them in the context of some quotations in both languages.